2012
DOI: 10.1016/s0377-1237(11)60125-1
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends of transfusion transmitted viral infections among blood donors in the last decade—a 10-year study in a large tertiary care blood bank (2000–2009

Abstract: There is a general reduction in the seroprevalence rate of viral infections. This is probably because of discouragement of professional or paid donations; better awareness, better prophylactic measures, and availability of vaccines have played a major role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
3
7
1
Order By: Relevance
“…Out of 2015 donations, males contributed to a larger percentage (96.5%) compared to females (3.5%), which is in concordance with the data given by a similar other study. [3] Syphilis (1.2%) was the most common TTI in the present study, which is in contrast to the data of other studies [1][2][3][4][5][10][11][12][13] where HBV was the most common TTI, and where as in the study by Kaur H et al [14] HCV was most the common TTI. None of the donor in our study was positive for HCV, but all other studies noted HCV prevalence of which Kaur H et al [14] had reported the highest HCV prevalence (1.79%).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Out of 2015 donations, males contributed to a larger percentage (96.5%) compared to females (3.5%), which is in concordance with the data given by a similar other study. [3] Syphilis (1.2%) was the most common TTI in the present study, which is in contrast to the data of other studies [1][2][3][4][5][10][11][12][13] where HBV was the most common TTI, and where as in the study by Kaur H et al [14] HCV was most the common TTI. None of the donor in our study was positive for HCV, but all other studies noted HCV prevalence of which Kaur H et al [14] had reported the highest HCV prevalence (1.79%).…”
Section: Discussioncontrasting
confidence: 99%
“…Philip CJ et al [12] 1.7% 0.7% 0.3% --Pallavi P et al [13] 1.27% 0.44% 0.23% 0.28% 0 Kaur H et al [14] 0.75% 0.16% 1.79% 0.67% 0 Fernandes H et al [15] 0.34% 0.06% 0.06% 0.11% 0.01% Present Study 0.84% 0.15% 0 1.29% 0.09%…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…There has subsequently been a significant and impressive reduction seen in HBV seroprevalence rate in blood donors from 2.39% in 2000 to 1.28% in 2009. 20 A similar decline of HBsAg prevalence in voluntary donors from 2000 to 2004 was noted by other workers. 21 Other factors which could have affected seroprevalence include deployment of troops in conflict zone and ethnicity of the troops.…”
Section: Hepatitis Bsupporting
confidence: 78%
“…These differences in testing methodology have resulted in the diagnosis of infection status with varying window periods, which do not allow a common interpretation of TTI results across different blood banks in the country. Most previous studies on TTIs in India have not been able to provide national level or even regional level analyses, but instead cover a limited number of blood banks [3]- [6]. A 10-year (2000-2009) study in a tertiary care center blood bank in Pune, India reported a significant decrease in transfusion transmissible viral infections, including HIV, HBsAg and HCV, among 51% replacement and 49% voluntary blood donors [3].…”
Section: Introductionmentioning
confidence: 99%